A study to assess the factors associated with developmental delay and nutritional status among the children with cleft lip and/or cleft palate - Sampagar, Abhilasha; Lakhkar, Bhavana; Bafna, Tanvi; Mahantashetti, Niranjana S (Indian Journal of Child Health, 2018)
Background: Cleft lip with or without cleft palate is one of the most common congenital anomalies. Development is often affected in these children. It may be due to other associated defects, syndromic status, or malnutrition. Objective: The objective of this study was to assess the factors associated with developmental delay and nutritional status among the children with cleft lip and/or cleft palate. Materials and Methods: A cross-sectional study was conducted at the Department of Pediatrics of a Medical College in Sawangi (Meghe), Wardha, for 2 years from August 2010 to March 2012. All children below 15 years with cleft lip and/or palate admitted in the pediatric ward, the neonatal intensive care unit, or postnatal ward were included in the study. A total of 200 children were included in the study and were analyzed for developmental delay and growth lag. Results: Cleft clip was seen in 51 (25.5%) of the children, 25 (12.5%) had cleft palate, and 124 (62%) had both cleft lip and palate. Developmental delay was more common in cleft palate category; however, it was not statistically significant (?2=0.90, p=0.34). Unilateral form of defects had more number of delays as compared to bilateral defects, and it was statistically significant (?2=7.32, p=0.006). Delay was more common when both the defects were present together as compared to isolated defects; however, it was not statistically significant. Gross motor and language delay were the most common type followed by global and personal social. 12.5% of children were syndromic. Most of the syndromic children (64%) had global developmental delay (?2=7.84, significant). 69.6% of children below the age group of 5 years were malnourished (?2=16, significant). Faulty feeding (73.5%), recurrent respiratory infections (21.4%), and repeated hospitalization (17.1%) were the statistically significant factors for poor growth. Conclusion: Global developmental delay was more common in syndromic children. Overall, delay was more commonly seen in children with unilateral defect. Factors, which contributed to growth lag, were faulty feeding, recurrent respiratory infections, and repeated hospitalization.